The importance of Personal Protective Equipment (PPE) on the construction site / Mohamad Aziz Izzuddin Baharom - Baharom, Mohamad Aziz Izzuddin (2015)
The construction industry is one industry that is very important and has an impact on the development process in Malaysia. Statistics of accidents and worker injuries at construction sites is high every year compared to other sectors. The parties involved in the construction industry strive continuously to reduce accidents and high mortality rates among workers at construction sites. Accidents at the construction site will still be an issue that is frequently reported in the media to this day. The topic of work safety is a very relevant and multifaceted problem for workers, firms and policy makers. Findings show poor working conditions are the most significant determinants of accidents and illnesses occurring at work, while having a fixed-term (temporary) contract is not significant. Other significant determinants of work safety are: not being new to the workforce; dissatisfaction with the current job; gender; and a latent proneness observed with occurrence of accident on the way to work.